Sphingosine kinase/sphingosine 1-phosphate axis: a new player for insulin-like growth factor-1-induced myoblast differentiation - Bernacchioni, Caterina (BioMed Central, 2012)
BACKGROUND: Insulin-like growth factor-1 (IGF-1) is the most important physiological regulator of skeletal muscle progenitor cells, which are responsible for adult skeletal muscle regeneration. The ability of IGF-1 to affect multiple aspects of skeletal muscle cell biology such as proliferation, differentiation, survival and motility is well recognized, although the molecular mechanisms implicated in its complex biological action are not fully defined. Since sphingosine 1-phosphate (S1P) has recently emerged as a key player in skeletal muscle regeneration, we investigated the possible involvement of the sphingosine kinase (SK)/S1P receptor axis on the biological effects of IGF-1 in murine myoblasts. METHODS: RNA interference, chemical inhibition and immunofluorescence approaches were used to assess the role of the SK/S1P axis on the myogenic and mitogenic effects of IGF-1 in C2C12 myoblasts. RESULTS: We show that IGF-1 increases SK activity in mouse myoblasts. The effect of the growth factor does not involve transcriptional regulation of SK1 or SK2, since the protein content of both isoforms is not affected; rather, IGF-1 enhances the fraction of the active form of SK. Moreover, transactivation of the S1P(2) receptor induced by IGF-1 via SK activation appears to be involved in the myogenic effect of the growth factor. Indeed, the pro-differentiating effect of IGF-1 in myoblasts is impaired when SK activity is pharmacologically inhibited, or SK1 or SK2 are specifically silenced, or the S1P(2) receptor is downregulated. Furthermore, in this study we show that IGF-1 transactivates S1P(1)/S1P(3) receptors via SK activation and that this molecular event negatively regulates the mitogenic effect elicited by the growth factor, since the specific silencing of S1P(1) or S1P(3) receptors increases cell proliferation induced by IGF-1. CONCLUSIONS: We demonstrate a dual role of the SK/S1P axis in response to myoblast challenge with IGF-1, that likely is important to regulate the biological effect of this growth factor. These findings add new information to the understanding of the mechanism by which IGF-1 regulates skeletal muscle regeneration.